FRI0140 EVALUATION OF EFFECTIVENESS AND USAGE PATTERNS OF TOFACITINIB IN TREATMENT OF RHEUMATOID ARTHRITIS IN AUSTRALIA: AN ANALYSIS FROM THE OPAL-QUMI REAL WORLD DATASET. (June 2019) - Bird, Paul; Littlejohn, Geoff; Butcher, Belinda; Smith, Tegan; Pereira, Candida Da Fonseca; Witcombe, David; Griffiths, Hedley
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Limited data from large real-world patient populations exist to describe treatment outcomes of patients who receive tofacitinib for the management of RA in Australia. Objectives: To evaluate effectiveness and treatment patterns of tofacitinib in a large real-world cohort of Australian adult patients with RA. Methods: Routinely collected, de-identified clinical data were sourced from the OPAL-QUMI dataset. Data from adult patients with a diagnosis of RA, who initiated treatment with tofacitinib or a bDMARD and had at least 12 months of follow–up between March 2015 and September 2018, were included. Descriptive analyses were performed on overall and propensity score matched populations. Treatment effectiveness was evaluated from baseline to month 18 by DAS28-ESR, SDAI and CDAI measures. Treatment persistence, in part a surrogate for efficacy, was estimated by Kaplan-Meier methods. Treatment pattern evaluation included percentage of patients receiving monotherapy or combination therapy at treatment initiation. Results: 1950 patients were included in the matched population (1300 bDMARD initiators; 650 tofacitinib initiators). Patients were predominantly aged 55 to 74 years (57.8%), and female (81.2%). At baseline, median disease duration was 107 and 120 months, with 16.1% and 17.3% of patients in DAS28-ESR defined disease remission for the bDMARD and tofacitinib groups respectively. After three months of treatment, 49.1% and 49.7% had achieved DAS remission and after 18 months of treatment, 52.4% and 57.8% of patients had achieved DAS remission in the bDMARD and tofacitinib groups respectively. At 18 months the percentage of patients achieving CDAI/SDAI remission was similar with 29.2%/29.0% bDMARD patients and 30.9%/30.5% tofacitinib patients reporting CDAI/SDAI remission respectively. The median persistence of treatment was similar for bDMARD and tofacitinib groups: 33.8 (95% CI 28.8 to 40.4) and 34.2 (95% CI 32.2 to not reached) months respectively. In the overall population, more patients were prescribed tofacitinib as monotherapy (43.4%) compared to bDMARD monotherapy (33.4%). Conclusion: In this analysis of a large real world dataset, tofacitinib demonstrated treatment effectiveness and persistence that was similar to bDMARDs. Overall, there was a trend for more use of tofacitinib as monotherapy than bDMARDs. Acknowledgement: We wish to acknowledge the Australian rheumatologists who contribute data to OPAL for research. Disclosure of Interests: Paul Bird Consultant for: Advisory boards for Eli Lily, Pfizer, Roche, AbbVie, Geoff Littlejohn Consultant for: Sat on Advisory Boards for AbbVie, Janssen, Roche, Pfizer, BMS, and Sanofi Genzyme, Belinda Butcher Consultant for: Consultant biostatistician and medical writer providing services to AbbVie, BMS, Janssen, MSD, Pfizer, UCB., Employee of: Janssen, Tegan Smith Grant/research support from: AbbVie, Consultant for: Provided medical writing services to Genentech, BioMarin, MSD, AbbVie, Roche, Actelion, Gilead, Kazia, Menarini, Candida da Fonseca Pereira Employee of: Pfizer, David Witcombe Shareholder of: Pfizer, Employee of: Pfizer, Hedley Griffiths Grant/research support from: Research funded by AbbVie, Janssen, BMS, Consultant for: Advisory boards for Sanofi, Pfizer, Novartis, Janssen